High‐Voltage Stability of Ionic‐Liquid‐Based Electrochemical Double Layer Capacitors with a Bimodal Porous Carbon Electrode. Issue 22 (19th September 2018) - Aref, Amir Reza; Rajagopalan, Ramakrishnan; Randall, Clive A.
Abstract: Micropores (<2 nm) and small mesopores (width between 2 and 10 nm) in the structure of carbon play an important role in determining both the charge storage properties and voltage stability of ionic‐liquid‐based electrochemical double layer capacitors (EDLCs). We demonstrate that the use of bimodal porous carbon electrodes results in excellent voltage stability and good capacitance retention (>90 %), as determined by using voltage holding tests at 3.5 V over 250 h. Furthermore, a three‐electrode split cell study showed that the voltage stability in bimodal carbon was achieved because of more symmetric potential distribution and similar electrode capacitances between the positive and negative electrodes as compared to purely microporous carbon electrode. The presence of larger mesopores (5–10 nm) in the bimodal carbon facilitates the access and rearrangement of the bulkier cations at the electrode/electrolyte interface, whereas this is severely hindered in purely microporous carbon electrode. By using a lumped transmission line model, we delineated the contribution of both smaller and larger pores in the bimodal carbon towards the impedance performance of EDLCs. Abstract : Pushing the limit : Hierarchical porosity in carbon electrodes affect the voltage stability of ionic‐liquid‐based electrochemical double layer capacitors. A three‐electrode study shows the influence of pore‐size distribution on the rest potential of the electrodes. Presence of micropores and mesopores in the carbon leads to more symmetric potential and capacitance distribution between the electrodes allowing them to stay within the electrochemical voltage stability limit of the ionic liquid.